ANALISIS PENGARUH MEDIA SOSIAL DALAM MENGIMPLEMENTASIKAN NILAI-NILAI PANCASILA TERHADAP GENERASI MUDA - Muhammad Ramadan; Igo Dwi Putra, Muhammad Rafi Alfath, Dimas Disa Pratama (Jurnal Komunikasi, 2024)
The development of the era in the digital world has resulted in digitalization in various fields. Community lifestyle patterns in digital developments have changed over time, one of which is the way of socializing which can now be done without having to meet face to face. Pancasila is currently experiencing a rise and fall of problems related to false news on political social media. Thus, as a young generation, it would be good to be able to use social media well and wisely. Apart from that, social media can be a forum for young people to implement Pancasila values in socializing in cyberspace. The research method used in this research is a normative legal approach. Data processing is carried out through library research, such as literature and scientific works related to research problems. The results of this research show that social media has an important role in influencing the younger generation in using social media to be able to implement the Pancasila values of the five existing principles. This is because social media plays a big role in shaping people's opinions and behavior, implementing Pancasila values such as tolerance, respecting individual rights, fostering unity in diversity, participating in a healthy democracy, and fighting for justice are very important. In this way, social media can be a positive tool in strengthening national unity, encouraging good ethics, and ensuring that the information disseminated on these platforms is in accordance with the principles of Pancasila